Self-Assembled Peptide Hydrogels PPI45 and PPI47: Novel Drug Candidates for Staphylococcus aureus Infection Treatment - Quanlong Wu; Mengyin Deng; Ruoyu Mao; Na Yang; Ya Hao; Manli Cao; Da Teng; Jianhua Wang (Gels)
Staphylococcus aureus, a prevalent zoonotic pathogen, poses a significant threat to skin wound infections. This study evaluates the bactericidal efficacy of self-assembled peptide hydrogels, PPI45 and PPI47, derived from the defensin-derived peptide PPI42, against S. aureus ATCC43300. The high-level preparation of PPI45 and PPI47 was achieved with yields of 1.82 g/L and 2.13 g/L, which are 2.19 and 2.60 times the yield of PPI42. Additionally, the critical micelle concentrations (CMCs) of the peptides at pH 7.4 for PPI42, PPI45, and PPI47 were determined to be 245 µg/mL, 973 µg/mL, and 1016 µg/mL, respectively. At a concentration of 3 mg/mL, the viscosities of the gels were 52,500 mPa·s, 33,700 mPa·s, and 3480 mPa·s for PPI42, PPI45, and PPI47. Transmission electron microscopy (TEM) revealed that all peptides exhibited long, pearl necklace-like protofibrils. These peptides demonstrated potent bactericidal activity, with a minimal inhibitory concentration (MIC) of 4–16 µg/mL against S. aureus, and a sustained effect post-drug clearance. Flow cytometry analysis after 2×MIC peptides treatment for 2 h revealed a 20–38% membrane disruption rate in bacteria, corroborated by scanning electron microscopy (SEM) observations of membrane damage and bacterial collapse. The peptide treatment also led to reduced hyperpolarized membrane potential. In vitro safety assessments indicated minimal hemolytic activity on murine red blood cells and low cytotoxicity on human immortalized epidermal cells (HaCaT). In summary, this work lays a valuable cornerstone for the future design and characterization of self-assembling antimicrobial peptides hydrogels to combat S. aureus infection.